High‐frequency temperature monitoring with time‐resolved wavelet analysis reveals unrecognized complexities across depth on a coral reef ecosystem - Aubrey Foulk; Tarik Gouhier; James Leichter; Alex S. J. Wyatt; Randi Rotjan; Mark Patterson; Brian Helmuth (Limnology and Oceanography, 2026)
Temperature variation at fine scales of minutes to hours and ~ 1–100 m is ubiquitous in marine ecosystems and often exceeds variability at larger scales. However, we know little of how well temperatures at one location or depth can serve as proxies to represent other locations, which is important in predicting thermal patterns relevant to organismal thermal stress. We used small data loggers to record fine‐scale temporal variability in water temperature across a depth gradient, over multiple years, on the barrier reef system in Belize. Using pairwise correlation and wavelet coherence, which quantifies the time‐ and frequency‐resolved correlation between pairs of time series, we examine how water temperature varies across reef zones (backreef, forereef inner, and forereef outer) and depths, and estimate the coherence of this variability across time scales. Although spectral analysis across the entire study period suggested a high degree of similarity in temperature patterns, time‐resolved wavelet analyses at daily, weekly, and monthly periodicities revealed significant differences across reef‐zone‐by‐depth combinations. We also detected a signal consistent with the Madden–Julian Oscillation. Coherence and phase locking at biologically relevant periodicities diminished with increasing depth difference between sites, suggesting that patterns at depth were not predictable from those near the surface. Overall, our findings show that wavelet analysis can reveal fine‐scale thermal variation on coral reefs that coarser sampling misses, and they make clear that accurately predicting how organismal performance will shift in space and time under global change depends on collecting and analyzing depth‐resolved, high‐frequency, in situ data wherever possible.

Amphipoda and the Riboviria: viral diversity on a global scale - Amy L. Burgess; Donald C. Behringer; Louisa E. Wood; Eunji Park; Randi Rotjan; Karina Scavo-Lord; Rebecca Branconi; Jamie Bojko (Journal of Invertebrate Pathology, 2026)

Larval Genomics as a Viable, Fisheries‐Independent Tool for Investigating Population Structure in Tropical Pacific Tunas - Jacob E. Jaskiel; Hannah E. Aichelman; Giulia Anderson; Louw Claassens; James E. Fifer; Christina M. Hernandez; Alexa K. Huzar; Joel K. Llopiz; Jan W. Witting; Sean P. Mullen; Randi D. Rotjan (Molecular Ecology, 2026)
Understanding how dispersal, life history, and environmental variability shape genetic connectivity in the open ocean remains a central challenge in evolutionary biology. Highly migratory marine predators like tunas have traditionally been considered genetically homogeneous across ocean basins, yet emerging genomic evidence suggests that cryptic population structure can persist even in species with high gene flow and large effective population sizes. We used 2bRAD sequencing of 348 larval and subadult skipjack ( Katsuwonus pelamis ), yellowfin ( Thunnus albacares ), and bigeye tuna ( T. obesus ) collected from the central Pacific across 7 years of sampling to examine species boundaries, population genetic information, genetic structure, and connectivity. Larval sampling revealed consistent spawning by all three species and enabled unbiased detection of genetic patterns prior to recruitment bottlenecks. We found strong divergence amongst species, no evidence of structuring within skipjack or bigeye, and a divergent yellowfin population detected in 2 consecutive sampling years north of American Samoa. Comparisons between larvae and subadults suggest that sampling early life history stages can be a valuable tool for assessing population genetic information before recruitment bottlenecks, selective harvest by fisheries, adult dispersal, and selective pressures acting on adult populations, thereby contributing novel insights to the research and effective management of these species. These results highlight how larval genomics can complement traditional population genomic studies of adult tunas and reveal fine‐scale structure in highly vagile species, providing new perspectives on connectivity in the open ocean.

The role of geological feature shape on the abundance and diversity of deep sea corals - Brian R.C. Kennedy; Randi D. Rotjan (Deep Sea Research Part I: Oceanographic Research Papers, 2026)

A review of the current knowledge of the flow of carbon and energy in scleractinian corals - Caroline F. Ianniello; Justin S. McAlister; Christine Ferrier-Pagès; Randi D. Rotjan (Coral Reefs, 2025)

Microplastic accumulation visually and fluorescently undetectable within deepwater corals of the remote equatorial Pacific - Maxwell S. Helmberger; Steven Auscavitch; Justin Linehan; Timothy M. Shank; Erik Cordes; Randi D. Rotjan (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Stress in the City: Disentangling multi-stressor effects on an urbanized coral in a changing ocean - Caroline F. Ianniello; Grace Beery; Ta-Hung (Denny) Chen; Ethan Deyle; Wendy Heiger-Bernays; Itasca Motter; Justin S. McAlister; Randi D. Rotjan (Marine Pollution Bulletin, 2025)

Microplastic abundance and accumulation patterns in eelgrass (Zostera marina L.) meadows throughout coastal Massachusetts, USA - Alyssa B. Novak; Cecelia M. Gerstenbacher; Karina Scavo Lord; Randi D. Rotjan (Environmental Monitoring and Assessment, 2024)

Mind the gap: comparing exploration effort with global biodiversity patterns and climate projections to determine ocean areas with greatest exploration needs - Brian R. C. Kennedy; Randi D. Rotjan (Frontiers in Marine Science, 2023)
The oceans contain 1,335 million km 3 of water covering 361.9 million km 2 of seafloor across 71% of the planet. In the past few decades, there has been substantial effort put into mapping and exploring the ocean fueled by the advent of new technologies that more easily enable deepwater access. However, we are still far from achieving our shared goals of a well characterized and documented ocean. In 2010, Webb et al. documented the paucity of deep-sea data in general, with a specific focus on the lack of pelagic records in the Ocean Biogeographic Information System OBIS, which is the largest of the ocean biodiversity archives. While significant exploration progress has been made, the rate of change in the ocean is outstripping the rate of characterization and research. Given the limited resources available, future work needs to be prioritized to focus on areas of greatest need. Here, we investigated several lines of inquiry to determine priority areas for future exploration. We accumulated the largest database of global deep submergence dive records ever compiled and used it, plus OBIS biodiversity records, to assess the level of exploration in different ocean regions. Then, we compared these measures of exploration effort with different biogeographic province schemas and estimates of climate change velocity projections to identify the largest remaining gaps in exploration and research sampling. Given that marine science has only explored between 5 and 20% of the ocean (depending on estimates) in the last hundred and fifty years, future exploration needs to be more targeted to attempt to keep pace with the rate and impact of environmental and biodiversity change in the ocean.

COBRA Master Class: Providing deep-sea expedition leadership training to accelerate early career advancement - Randi D. Rotjan; Katherine L. C. Bell; Julie A. Huber; Charles Geoffrey Wheat; Andrew T. Fisher; Rosalynn Lee Sylvan; James McManus; Katharine T. Bigham; Sergio Cambronero-Solano; Tristan Cordier; Savannah Goode; Juliana Leonard; et al. (Frontiers in Marine Science, 2023)
Leading deep-sea research expeditions requires a breadth of training and experience, and the opportunities for Early Career Researchers (ECRs) to obtain focused mentorship on expedition leadership are scarce. To address the need for leadership training in deep-sea expeditionary science, the Crustal Ocean Biosphere Research Accelerator (COBRA) launched a 14-week virtual Master Class with both synchronous and asynchronous components to empower students with the skills and tools to successfully design, propose, and execute deep-sea oceanographic field research. The Master Class offered customized and distributed training approaches and created an open-access syllabus with resources, including reading material, lectures, and on-line resources freely-available on the Master Class website (cobra.pubpub.org). All students were Early Career Researchers (ECRs, defined here as advanced graduate students, postdoctoral scientists, early career faculty, or individuals with substantial industry, government, or NGO experience) and designated throughout as COBRA Fellows. Fellows engaged in topics related to choosing the appropriate deep-sea research asset for their Capstone “dream cruise” project, learning about funding sources and how to tailor proposals to meet those source requirements, and working through an essential checklist of pre-expedition planning and operations. The Master Class covered leading an expedition at sea, at-sea operations, and ship-board etiquette, and the strengths and challenges of telepresence. It also included post-expedition training on data management strategies and report preparation and outputs. Throughout the Master Class, Fellows also discussed education and outreach, international ocean law and policy, and the importance and challenges of team science. Fellows further learned about how to develop concepts respectfully with regard to geographic and cultural considerations of their intended study sites. An assessment of initial outcomes from the first iteration of the COBRA Master Class reinforces the need for such training and shows great promise with one-quarter of the Fellows having submitted a research proposal to national funding agencies within six months of the end of the class. As deep-sea research continues to accelerate in scope and speed, providing equitable access to expedition training is a top priority to enable the next generation of deep-sea science leadership.

Low-Cost, Deep-Sea Imaging and Analysis Tools for Deep-Sea Exploration: A Collaborative Design Study - Katherine L. C. Bell; Jennifer Szlosek Chow; Alexis Hope; Maud C. Quinzin; Kat A. Cantner; Diva J. Amon; Jessica E. Cramp; Randi D. Rotjan; Lehua Kamalu; Asha de Vos; Sheena Talma; Salome Buglass; et al. (Frontiers in Marine Science, 2022)
A minuscule fraction of the deep sea has been scientifically explored and characterized due to several constraints, including expense, inefficiency, exclusion, and the resulting inequitable access to tools and resources around the world. To meet the demand for understanding the largest biosphere on our planet, we must accelerate the pace and broaden the scope of exploration by adding low-cost, scalable tools to the traditional suite of research assets. Exploration strategies should increasingly employ collaborative, inclusive, and innovative research methods to promote inclusion, accessibility, and equity to ocean discovery globally. Here, we present an important step toward this new paradigm: a collaborative design study on technical capacity needs for equitable deep-sea exploration. The study focuses on opportunities and challenges related to low-cost, scalable tools for deep-sea data collection and artificial intelligence-driven data analysis. It was conducted in partnership with twenty marine professionals worldwide, covering a broad representation of geography, demographics, and domain knowledge within the ocean space. The results of the study include a set of technical requirements for low-cost deep-sea imaging and sensing systems and automated image and data analysis systems. As a result of the study, a camera system called Maka Niu was prototyped and is being field-tested by thirteen interviewees and an online AI-driven video analysis platform is in development. We also identified six categories of open design and implementation questions highlighting participant concerns and potential trade-offs that have not yet been addressed within the scope of the current projects but are identified as important considerations for future work. Finally, we offer recommendations for collaborative design projects related to the deep sea and outline our future work in this space.

Historical Trends of Sperm Whale (Physeter macrocephalus) Distribution in the Phoenix Archipelago - Brian R. C. Kennedy; Lara Hakam; Jan Witting; Regen Milani; Sue Taei; Tim Smith; Erin Taylor; Tooreka Teemari; Randi D. Rotjan (Frontiers in Marine Science, 2021)
The Phoenix Archipelago in the Central Pacific is situated in what was once one of the most productive areas for capturing sperm whales ( Physeter macrocephalus ). These whales were the focal targets of American offshore whalers in the mid-19th century along the equator, an area known as the “on-the-line” whaling grounds. Now, as large-scale Marine Protected Areas (MPAs) have provided protection for marine mammals and their food sources, it is important to have a solid understanding of historical baselines so recovery distributions can be compared with pre-whaling distributions. The Phoenix Islands archipelago contains two large MPAs: the Phoenix Islands Protected Area (PIPA), established by Kiribati in 2008, and the Howland/Baker unit of the Pacific Remote Islands Marine National Monument (PRIMNM), established by the United States in 2009. Using historic whaling records from American whaling vessels operated through the wider Phoenix Archipelago region, we reconstructed information about the presence and distribution of P. microcephalus throughout the 1800s within and around PIPA and the Howland/Baker units of the PRIMNM. Historical data analyzed using ArcGIS showed that sperm whales were present year-round within the study area, which is consistent with 20th century records from the Ocean Biogeographic Information System (OBIS). A Getis Ord Gi ∗ hotspot analysis also revealed sighting hotspots within PIPA and near Howland and Baker, suggesting that these two areas may be of long-term ecological importance to sperm whales in the central Pacific. The New England whaling fleet ceased whaling effort in the central Pacific in the late 1800s, and publicly available records since that time are scarce. There has been no modern systematic whale survey ever conducted within the Phoenix Archipelago, though anecdotal accounts and sightings have been compiled over the years. These intermittent accounts suggest that though whale populations have not recovered to pre-whaling baselines, large-scale MPAs may play a role in helping to foster a resurgence of marine mammal populations. As the network of large-scale MPAs continue to grow as part of the commitment to ocean conservation set forth by UNESCO, IUCN, and the UN Decade for Ocean Science, historical baselines will be critical as a “yardstick” to measure population resurgence success for each MPA, and for populations overall.

Deep-Sea Debris in the Central and Western Pacific Ocean - Diva J. Amon; Brian R. C. Kennedy; Kasey Cantwell; Kelley Suhre; Deborah Glickson; Timothy M. Shank; Randi D. Rotjan (Frontiers in Marine Science, 2020)

Corrigendum: The Unknown and the Unexplored: Insights Into the Pacific Deep-Sea Following NOAA CAPSTONE Expeditions - Brian R. C. Kennedy; Kasey Cantwell; Mashkoor Malik; Christopher Kelley; Jeremy Potter; Kelley Elliott; Elizabeth Lobecker; Lindsay McKenna Gray; Derek Sowers; Michael P. White; Scott C. France; Steven Auscavitch; et al. (Frontiers in Marine Science, 2020)

Oceanographic Drivers of Deep-Sea Coral Species Distribution and Community Assembly on Seamounts, Islands, Atolls, and Reefs Within the Phoenix Islands Protected Area - Steven R. Auscavitch; Mary C. Deere; Abigail G. Keller; Randi D. Rotjan; Timothy M. Shank; Erik E. Cordes (Frontiers in Marine Science, 2020)

Correction to: Skeletal records of bleaching reveal different thermal thresholds of Pacific coral reef assemblages - Nathaniel R. Mollica; Anne L. Cohen; Alice E. Alpert; Hannah C. Barkley; Russell E. Brainard; Jessica E. Carilli; Thomas M. DeCarlo; Elizabeth J. Drenkard; Pat Lohmann; Sangeeta Mangubhai; Kathryn R. Pietro; Hanny E. Rivera; et al. (Coral Reefs, 2019)

The Unknown and the Unexplored: Insights Into the Pacific Deep-Sea Following NOAA CAPSTONE Expeditions - Brian R. C. Kennedy; Kasey Cantwell; Mashkoor Malik; Christopher Kelley; Jeremy Potter; Kelley Elliott; Elizabeth Lobecker; Lindsay McKenna Gray; Derek Sowers; Michael P. White; Scott C. France; Steven Auscavitch; et al. (Frontiers in Marine Science, 2019)

Skeletal records of bleaching reveal different thermal thresholds of Pacific coral reef assemblages - Nathaniel R. Mollica; Anne L. Cohen; Alice E. Alpert; Hannah C. Barkley; Russell E. Brainard; Jessica E. Carilli; Thomas M. DeCarlo; Elizabeth J. Drenkard; Pat Lohmann; Sangeeta Mangubhai; Kathryn R. Pietro; Hanny E. Rivera; et al. (Coral Reefs, 2019)

The effect of coral restoration on Caribbean reef fish communities - Ann H Opel; Colleen M Cavanaugh; Randi D Rotjan; Joey Pakes Nelson (Marine Biology, 2017)

Spatially distinct and regionally endemic Symbiodinium assemblages in the threatened Caribbean reef-building coral Orbicella faveolata - Dustin W. Kemp; Daniel J. Thornhill; Randi D. Rotjan; Roberto Iglesias-Prieto; William K. Fitt; Gregory W. Schmidt (Coral Reefs, 2015)

Short-term changes of fish assemblages observed in the near-pristine reefs of the Phoenix Islands - Sangeeta Mangubhai; Ayron M. Strauch; David O. Obura; Gregory Stone; Randi D. Rotjan (Reviews in Fish Biology and Fisheries, 2014)

Predators selectively graze reproductive structures in a clonal marine organism - Randi D. Rotjan; Sara M. Lewis (Marine Biology, 2009)

Chronic parrotfish grazing impedes coral recovery after bleaching - Randi D. Rotjan; James L. Dimond; Daniel J. Thornhill; James J. Leichter; Brian Helmuth; Dustin W. Kemp; Sara M. Lewis (Coral Reefs, 2006)

Shell choice in Pagurus longicarpus hermit crabs: does predation threat influence shell selection behavior? - Randi D. Rotjan; Julia Blum; Sara M. Lewis (Behavioral Ecology and Sociobiology, 2004)